STRATEGI MANAJEMEN DATA YANG EFEKTIF UNTUK MENINGKATKAN KINERJA BASIS DATA - Nursgustin; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2024)
In an increasingly connected and complex business environment, implementing effective data management strategies is crucial for improving database performance. This article provides an overview of various strategies that can be used to improve database performance, including proper indexation, intelligent data partitioning, and query optimization. Implementation of this strategy can lead to increased operational efficiency and responsiveness of database systems.